TINJAUAN STANDART KESTABILAN TOWER NG STANDAR 30 METER TERHADAP BEBAN GEMPA DINAMIS DENGAN BERBAGAI SITUS KELAS TANAH SESUAI SNI 1726-2012 - Sudarmaji, Sigid Bayu; Muhtar, Muhtar; Priyono, Pujo (HEXAGON, 2020)
The development of world telecommunications is growing very rapidly occur today, requires the telecommunications provider to provide a means of expanding the reach of mobile phone signal and internet signal in the form of 2G, 3G and 4G. With it the necessary means of supporting specialized tower BTS (Base Transceiver Station) to carry the antenna ata certain height.In planning the establishment of the BTS tower. The load effect in the form of self weight live load and wind load. But necessary review of the value of the Twist, Sway, and Displacement due to earthquake loads that occur with a variety of site classes of the soil in the form of rock soil, hard soil, medium soil and soft soil in accordance with SNI 1726-2012.